Protective camouflage cover - Golodyaev, Alexander Ivanovich (Vojnotehnički glasnik / Military Technical Courier, 2014)
Uniformity of protective camouflage installations significantly increases survivability of tanks on the move. This installation prevents an enemy from distinguishing a tank from a car or an empty trailer. A camouflage cover made of multilayer water-resistant material makes anti-tank shaped charge projectiles pre-detonate. Since most projectiles are designed for attacking ERA, the first detonation hits the camouflage cover instead of the armour. When the second detonation hits the ERA, its explosion neutralizes the shaped charge jet. This structure is considerably cheaper and much more effective than rubber protection models. The article analyses anti-tank combat means, “smart” missile guidance methods and methods of fighting means of attack. It also gives methods of fighting “smart” projectiles and the applications of this protective camouflage structure.
Keywords: camouflage; protection of armoured vehicles; decoys